A combined chemical and bioassay analysis of traffic-emitted polycyclic aromatic hydrocarbons - Ciganek, M; Neca, J; Adamec, V; Janosek, J; Machala, M (The Science of the total environment, 2004)
The objective of this study was to determine the concentrations of an extended series of polycyclic aromatic hydrocarbons (PAHs) and nitrated PAHs in outdoor air samples collected in low-contaminated urban areas, affected mainly by traffic emissions, and to estimate in vitro mutagenic and dioxin-like toxicity of extracts from these samples. Data on concentrations of PAHs and toxic in vitro potencies were compared in extracts obtained by different sampling methods. PAHs and their derivatives were analysed by high performance liquid chromatography with diode array and fluorescence detection, as well as gas chromatography with mass spectrometry. The total sum of 39 PAHs under study ranged from 6.7 to 62.7 ng.m(-3); of this, the sum of 16 U.S. EPA priority PAHs in urban air samples ranged from 3.2 to 6.2 ng.m(-3). Phenanthrene was the prevalent PAH in all air samples tested, with concentrations up to 17.6 ng.m(-3), followed by fluorene, fluoranthene and pyrene present mostly in the gaseous phase. Also, other low molecular weight PAHs (with MW up to 228) were distributed mostly in gaseous phase. The particulate phase contained mostly carcinogenic PAHs, among which, benzo[a]pyrene, indeno[1,2,3-cd]pyrene and benzofluoranthenes were predominant compounds (with benzo[a]pyrene reaching levels up to 1.57 ng.m(-3)). Traffic emissions were confirmed as the major source of PAHs in the airborne samples due to the presence of elevated concentrations of benzo[ghi]perylene and coronene. The most abundant nitrated PAH derivatives were nitronaphthalenes, which were present exclusively in the vapor phase; 9-nitroanthracene, 9-nitrophenantrene and 3-nitrofluoranthene were associated mostly with particulate matter (PM(10)). Bioassays for detection of the Ah receptor-mediated activity and mutagenicity in vitro were used as a screen of potential adverse effects of air pollutants emitted from traffic. The major part of mutagenic and aryl hydrocarbon receptor (AhR)-mediated activities was found to be present in the PM(10) fraction. Although the PM(10) sampling technique was found to be a suitable method regarding the subsequent determination of mutagenic and AhR-mediated activities in vitro, relative toxic potencies, associated with low molecular weight PAHs (such as tumor promotion and other adverse effects), could be underestimated.
Keywords: biotest; DNA Damage; Mutagenicity Tests; Cities; výfukové emise vozidel; monitorování životního prostředí; velkoměsta; vysokoúčinná kapalinová chromatografie; receptory aromatických uhlovodíků; Vehicle Emissions; testy genotoxicity; Salmonella typhimurium; Chromatography, High Pressure Liquid; Receptors, Aryl Hydrocarbon; poškození DNA; plynová chromatografie s hmotnostně spektrometrickou detekcí; polycyklické aromatické uhlovodíky; Environmental Pollutants; Polycyclic Aromatic Hydrocarbons; Biological Assay; Environmental Monitoring; Gas Chromatography-Mass Spectrometry; látky znečišťující životní prostředí